A novel insertion mutation in the cartilage-derived morphogenetic protein-1 (CDMP1) gene underlies Grebe-type chondrodysplasia in a consanguineous Pakistani family - Ansar Muhammad; Ali Ghazanfar; Wasif Naveed; Naqvi Syed; Basit Sulman; Ahmad Wasim (BMC, 2008)
Abstract Background Grebe-type chondrodysplasia (GCD) is a rare autosomal recessive syndrome characterized by severe acromesomelic limb shortness with non-functional knob like fingers resembling toes. Mutations in the cartilage-derived morphogenetic protein 1 (CDMP1) gene cause Grebe-type chondrodysplasia. Methods Genotyping of six members of a Pakistani family with Grebe-type chondrodysplasia, including two affected and four unaffected individuals, was carried out by using polymorphic microsatellite markers, which are closely linked to CDMP1 locus on chromosome 20q11.22. To screen for a mutation in CDMP1 gene, all of its coding exons and splice junction sites were PCR amplified from genomic DNA of affected and unaffected individuals of the family and sequenced directly in an ABI Prism 310 automated DNA sequencer. Results Genotyping results showed linkage of the family to CDMP1 locus. Sequence analysis of the CDMP1 gene identified a novel four bases insertion mutation (1114insGAGT) in exon 2 of the gene causing frameshift and premature termination of the polypeptide. Conclusion We describe a 4 bp novel insertion mutation in CDMP1 gene in a Pakistani family with Grebe-type chondrodysplasia. Our findings extend the body of evidence that supports the importance of CDMP1 in the development of limbs.